Improvement of Business Management for SMEs Through Integrated Assitance (ABDIMAS: Jurnal Pengabdian Masyarakat, 2023)
In the current pandemic conditions, the vanguard as a driving force for the economy is SMEs. The spread of SMEs. The current household scale cannot be separated from an urge to rise in the current pandemic situation. UKM "Opik Jan" is one of the household-scale SMEs engaged in the food and beverage sector and the establishment of this UKM cannot be separated from the provision of a capital Bank. Therefore, business owners have a big responsibility to continue to develop efforts. However, in this business development effort, UKM owners are also required to change their strategy for running their businesses. But limited knowledge becomes an obstacle for business owners. The problem faced is the inappropriateness of the use of production and packaging equipment so that it is vulnerable to bacterial contamination, packaging labels are not yet available so that the marketing scope cannot widely affordable, and the absence of simple bookkeeping records results in business owners not know the financial position of the business owned. These are the inhibiting factors in business development. The purpose of this community service activity is to provide education, knowledge, and motivation related to SME business development. Community service activities are carried out in the form of training and assistance in the use of fryers for production, packaging and labeling, and simple bookkeeping. Methods of implementation in the form of observation, preparation, delivery of material face to face, mentoring, training, and evaluation. The result of the implementation of community service is that participants already have frying pans, labels, and packaging on products, and business owners already have simple bookkeeping records for daily transactions.